Mengukur Tingkat Kapabilitas Tata Kelola Teknologi Informasi di Universitas Pasundan Bandung - Prayoga Adhi Pangestu (Jurnal Syntax Admiration, 2023)
The purpose of Pasundan University Bandung (UNPAS) in organizing good information technology governance is to form an agency called SPTIK (Information and Communication Technology Management Unit) in which there are various services, one of which is the online New Student Admission (PMB) service. The initial stage in measuring the level of capability of online PMB services is to study the UNPAS SPTIK document and other supporting documents related to PMB services, make observations on PMB activities, determine questions that will be used as a reference in determining the capability value and determine expert respondents to be interviewed. The results of the interview were processed using COBIT 5 as a guideline to measure the level of PMB service capability and resulted in an online PMB service capability level of 21% and is at level 1 in the sense that there is some evidence of attribute achievement in the process assessment, but some aspects of the assessment of attribute achievement may not be known to be true. In addition, the results of analysis and recommendations are made as a reference in improving the performance of these services.